ERO1α inhibits cell apoptosis and regulates steroidogenesis in mouse granulosa cells. (1st July 2020) - Hu, Jiahui; Jin, Jiaqi; Qu, Yuxing; Liu, Wanyang; Ma, Zhiyu; Zhang, Jinlong; Chen, Fenglei
Abstract: ER oxidoreduclin 1α (ERO1α), an oxidase that exists in the ER, participates in protein folding and secretion and inhibiting apoptosis, and regulates tumor progression, which is a novel factor of poor cancer prognosis. However, the other physiological functions of ERO1α remain undiscovered. Although our preliminary results of this study indicated that ERO1α revealed the robust expression in ovary, especially in granulosa cells, the role of ERO1α in follicular development is not well known. Therefore, the aims of the present study were to explore the role of ERO1α and the possible mechanisms in regulating cell apoptosis and steroidogenesis in ovarian granulosa cells. ERO1α was mainly localized in granulosa cells and oocytes in the adult ovary by immunohistochemistry. Western blot analysis showed that the expression of ERO1α was highest at oestrous stage during the estrous cycle. The effect of ERO1α on cell apoptosis and steroidogenesis was detected by transduction of ERO1α overexpression and knockdown lentiviruses into primary cultured granulosa cells. Flow cytometry analysis showed that ERO1α decreased granulosa cells apoptosis. Western bolt and RT-qPCR analysis found that ERO1α increased the ratio of BCL-2/BAX, and decreased BAD and Caspase-3 expression. ELISA analysis showed that ERO1α enhanced estrogen (E2) secretion. Western bolt and RT-qPCR analysis found that ERO1α increased StAR, CYP11A1, 3β-HSD, CYP17A1, and CYP19A1 expression, and decreased CYP1B1 expression. Furthermore, Western bolt analysis found that ERO1αincreased PDI and PRDX 4 expression, and activated the PI3K/AKT/mTOR signaling pathway through increasing the phosphorylation of AKT and P70 S6 kinase. In summary, these results suggested that ERO1α might play an anti-apoptotic role and regulate steroidogenesis in granulosa cells, at least partly, via activation of the PI3K/AKT/mTOR signaling pathway. Highlights: ERO1α inhibits apoptosis via inhibition of the mitochondrial-mediated apoptotic pathway. ERO1α regulates steroidogenesis via promotion of hormone synthesis and inhibition of hormone degradation. ERO1α regulates apoptosis and hormone secretory, at least partly, via activation of the PI3K/AKT/mTOR pathway.